Economics of moderation. Towards sustainable development - Siuta-Tokarska, Barbara (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The article describes attempts at implementation of the idea of sustainable development in the world economy of the 21st century. The presented research is theoretical. The aim of the study is to set economics of moderation as a theory in the evolution of economic thought. The problem of sustainable development in the world economy has been depicted in relation to ongoing environmental, social and economic changes, pointing to the negative effects of the implementation of the current consumption model of contemporary economies. “Economics of moderation” is a new, unique approach to the theory of economics forming some kind of theoretical basis to the practical implementation of a real development restoring the right understanding of intergenerational harmony and justice. In the research work, an analysis of the literature on the subject, both domestic and foreign, was used within the scope of research methods of social sciences in the field of analysis and criticism of literature, as well as analysis and logical construction.

W artykule podjęty został problem realizacji zrównoważonego rozwoju w gospodarce światowej XXI wieku. Przedstawiona praca ma charakter teoretyczny. Celem publikacji jest przedstawienie ekonomii umiaru jako teorii w kontekście ewolucji myśli ekonomicznej w głównym nurcie ekonomii rozwoju. Zagadnienie to zostało ukazane w relacji do postępujących zmian środowiskowych, społecznych i ekonomicznych, ze wskazaniem na negatywne skutki realizacji obowiązującego konsumpcyjnego modelu współczesnych gospodarek. „Ekonomia umiaru” to swoiste nowe spojrzenie na teorię ekonomii, która daje podstawy teoretyczne do przejścia w rzeczywistą, praktyczną realizację rozwoju, przywracającego właściwe pojmowanie ładu i sprawiedliwości międzypokoleniowej. Na potrzeby realizacji niniejszych badań wykorzystano analizę literatury przedmiotu zarówno krajowej, jak i zagranicznej w obrębie metod badawczych nauk społecznych z zakresu analizy i krytyki piśmiennictwa, a także analizy i konstrukcji logicznej.
Keywords: economy; moderation; sustainable development; ekonomia; umiar; zrównoważony rozwój